Is Disclosure an Effective Cleansing Mechanism? The Dynamics of Compensation Peer Benchmarking - Faulkender, Michael; Yang, Jun (Review of Financial Studies, 2013)
[Firms routinely justify CEO compensation by benchmarking against companies with highly paid CEOs. We examine whether the 2006 regulatory requirement of disclosing compensation peers mitigated firms' opportunistic peer selection activities. We find that strategic peer benchmarking did not disappear after enhanced disclosure. In fact, it intensified at firms with low institutional ownership, low director ownership, low CEO ownership, busy boards, large boards, and non-intensive monitoring boards, and at firms with shareholders complaining about compensation practices. The effect is also stronger at firms with new CEOs. These findings call into question whether disclosure regulation can remedy potential problems in compensation practices.]